Substantial changes in synaptic firing frequencies induced by glial ATP hysteresis - Noori, Hamid Reza (Biosystems, 2011)
Recent experimental studies strongly suggest the influence of glial purinergic transmission in the modulation of synaptic dynamics. By releasing adenosine triphosphate (ATP), which accumulates as adenosine, astrocytes tonically suppressed synaptic transmission. The delayed multi-step feedback of the glial ATP with the neuron suggests the existence of a discrete hysteresis phenomena. By integration of this hysteretic behavior into a delayed leaky integrate-and-fire model for the tripartite synapses, a significant sensitivity of the pre- and postsynaptic firing frequency patterns to the adenosine feedback-delays is observed that might be of importance for adenosine-related neurological deficits, such as sleep disorders.
Gesehen am 28.09.2022